ANALISIS SEMANTIK CERPEN BALI MODERN BERUNG KAPANTEG NGAAD - Ari Plasa Octoyota (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2022)
Abstract Bali has a complex language structure and the classification of the language used by its speakers is called Sor Singgih Basa Bali. This is a challenge and uniqueness for Balinese speakers when applying it in a literary work or in everyday life. There are various modern literary works that continue to be developed, one of which is the modern Balinese short story. In this study, a descriptive-qualitative semantic analysis of the short story Berung Kapanteg Ngaad by Anak Agung Gede Wiraputra will be discussed. Sources of data or written data obtained from the short story Berung Kapanteg Ngaad and supporting data from various other sources. The results showed that the meaning contained in the short story of Berung Kapanteg Ngaad is lexical meaning, grammatical meaning, and figurative meaning. These meanings reflect the situation of Balinese people as speakers of Balinese regional languages ​​which have language complexity and classification. So that it has a variety of languages ​​and reflects the uniqueness of the culture behind the phenomenon of society, which is clearly stated by the author in a literary work, namely modern Balinese short stories. Keywords: Semantics, Modern Balinese Short Story, Berung Kapanteg Ngaad